Chlorhexidine bathing and Clostridium difficile infection in a surgical intensive care unit - Bui, L; Swan, J; Shirkey, B; Olsen, R; Long, S; Graviss, E (Elsevier, 2018)
Background Clostridium difficile is the most common causative pathogen for hospital-acquired infections in the intensive care unit. This study evaluated the effect of chlorhexidine bathing every other day in preventing hospital-acquired C. difficile infection (CDI) using data from the CHlorhexidine Gluconate BATHing (CHG-BATH) randomized trial. Methods The primary endpoint was the proportion of patients acquiring CDIs among patients at risk for incident CDIs. Infections detected >48 h after randomization were classified as incident CDIs. Infections detected before or within 48 h of randomization were classified as prevalent CDIs. Results Of 38 patients (11.7%) who met criteria for potential CDI and underwent adjudication, 24 (7.4%) received oral or enema vancomycin, 18 (5.5%) had a positive C. difficile molecular assay, 14 (4.3%) received an International Classification of Diseases, Ninth Revision, Clinical Modification code for CDI, and 2 (0.6%) had possible pseudomembranous colitis on histopathology reports. The prevalence of CDI was 3.7% (6 of 164) in the soap and water arm and 4.3% (7 of 161) in the chlorhexidine arm. Compared with daily soap and water bathing, 2% chlorhexidine bathing every other day was not associated with the prevention of hospital-acquired CDI (1.3% [2 of 152] soap and water versus 2.0% [3 of 148] chlorhexidine, P = 0.68). Conclusions It is inconclusive if there was an association between chlorhexidine bathing and incidence of CDI among surgical intensive care unit patients in this study as statistical power was limited. There are limited published data evaluating the association between chlorhexidine bathing and CDI, and this study provides data for future systematic reviews and meta-analyses.